(untitled) (International Association of Biologicals and Computational Digest, 2022)
Withania somnifera (L.) Dunal is a well-known and important medicinal plant widely used in several indigenous systems of medicine for the treatment of various ailments, viz. asthma, bronchitis, inflammatory diseases, ulcer and stomach problems. Steroidal lactones have been reported as the major phytoconstituents of this species. Different pharmacological experiments in a number of in vitro and in vivo models have convincingly demonstrated the ability of W. somnifera to exhibit anti-inflammatory, anti-oxidative, antimicrobial, anti-anxiety, aphrodisiac, immunomodulation, anti- diabetic, anti-ulcer, anticancer, central nervous system depressant and hepatoprotective activities, lending support to the rationale behind several of its traditional uses. The species is also used to treat some neurological disorders like Parkinson’s and Alzheimer’s. The phytochemicals such as withaferin A, withanolide A and withanolide D isolated from this plant are potential bioactive molecules. Due to the remarkable biological activity of W. somnifera and its constituents, it will be appropriate to develop them as a medicine and make them more potent by chemical modifications and biotransformation. This review has covered botany, chemistry and pharmacology of the plant besides its traditional and folkloric uses.